2018
DOI: 10.1177/1087054718797434
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the French Version of the Weiss Functional Impairment Rating Scale–Self-Report in a Large Cohort of Adult Patients With ADHD

Abstract: The French version of the WFIRS-S is a psychometrically acceptable self-reported questionnaire for the multi-domain evaluation of functional impairments in adults with ADHD, for research and clinical purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…This is consistent with clinical research demonstrating that ADHD is highly related to functional impairment in the school arena as well as affecting adolescents' self-esteem [5,6]. This pattern in WFIRS-S is similar to patterns presented in American, French and Japanese validation studies of college students and adults with ADHD [22,24,25]. Unfortunately, there are no comparable studies to date of clinical adolescent ADHD populations; however, a WFIRS-S validation study of Iranian adolescents with no ADHD found results similar to ours, with self-concept being the most impaired domain [23].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with clinical research demonstrating that ADHD is highly related to functional impairment in the school arena as well as affecting adolescents' self-esteem [5,6]. This pattern in WFIRS-S is similar to patterns presented in American, French and Japanese validation studies of college students and adults with ADHD [22,24,25]. Unfortunately, there are no comparable studies to date of clinical adolescent ADHD populations; however, a WFIRS-S validation study of Iranian adolescents with no ADHD found results similar to ours, with self-concept being the most impaired domain [23].…”
Section: Discussionsupporting
confidence: 88%
“…The item-to-factor loadings were all above 0.30 which is the minimum standard of itemconvergent validity [51]. The results support the original factor structure in the questionnaires and are in line with validation studies in other languages [19,[21][22][23][24]. For clinical practice, we suggest the first-order solution to be the more relevant model, since the inspection of impairment across different domains is useful both for diagnostic purposes, as well as targeting treatment intervention for the individual patient.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Psychometric properties of the WFIRS-S, including construct validity, internal structural validity, and external validity, have been tested in several studies [42,43]. Cronbach's alpha coefficients obtained for the overall scale have been high (.91).…”
Section: Functional Impairmentmentioning
confidence: 99%
“…The WFIRS 16 is a self-report scale, designed to assess ADHD-related functional impairment in seven domains that are clinically relevant to ADHD in adulthood, including home, self-concept, learning & work, activities of daily living (ADLs), social activities, and risky activities 16,18,19 . These domains are likely to represent the target for treatment, meaning the use of the scale before and after treatment can determine improvements in the service user's ADHD, as well as whether functional difficulties have been alleviated 19 .…”
Section: Methodsmentioning
confidence: 99%